Pendampingan Masyarakat dalam Perencanaan Penataan Permukiman Kumuh di Kampung Pedak Baru, Bantul - Bawole, Paulus; Sutanto, Haryati (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Architectural works of poor communities in informal settlements are often recoqnized as Marginalized Architecture, because indeed the people who create the Architecture is in these settlements are people who are marginalized by the social strata of urban society. They develop the house according to their needs and abilities. Methods of development, planning and design as well as the use of building materials are often very suitable for the needs of the local community, the local climate and even according to their daily income. In SDGs 2030 it is hoped that the settlements of these marginal communities can be eliminated. One of the marginal settlements in Bantul Regency is located in Kampung Pedak Baru, Bangun Tapan Village. The situation of marginal settlements developed on the banks of the Gajahwong river needs to be developed. Through community assistance conducted by lecturers from Duta Wacana Christian University, community-based slum settlement planning was carried out. With a totally participatory planning model, this community service program can be implemented well together with the team KOTAKU program supported by the Bantul Regency regional government. As a result of the total participatory model in planning slum development, the people of Kampung Pedak Baru are satisfied because they were involved in the planning process. Apart from that, currently the Bantul Regency Government is still negotiating with the Central Government to finance the implementation of the slum area development plan in Kampung Pedak Baru. Architectural works of poor communities in informal settlements are often recoqnized as Marginalized Architecture, because indeed the people who create the Architecture is in these settlements are people who are marginalized by the social strata of urban society. They develop the house according to their needs and abilities. Methods of development, planning and design as well as the use of building materials are often very suitable for the needs of the local community, the local climate and even according to their daily income. In SDGs 2030 it is hoped that the settlements of these marginal communities can be eliminated. One of the marginal settlements in Bantul Regency is located in Kampung Pedak Baru, Bangun Tapan Village. The situation of marginal settlements developed on the banks of the Gajahwong river needs to be developed. Through community assistance conducted by lecturers from Duta Wacana Christian University, community-based slum settlement planning was carried out. With a totally participatory planning model, this community service program can be implemented well together with the team KOTAKU program supported by the Bantul Regency regional government. As a result of the total participatory model in planning slum development, the people of Kampung Pedak Baru are satisfied because they were involved in the planning process. Apart from that, currently the Bantul Regency Government is still negotiating with the Central Government to finance the implementation of the slum area development plan in Kampung Pedak Baru.